2016
DOI: 10.1590/1678-775720160214
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of fine-needle aspiration cytology for diagnosis of parotid gland masses: a clinicopathological study of 114 patients

Abstract: Objective Fine-needle aspiration cytology is a valuable method for preoperative assessment of head and neck tumors. However, its accuracy in detection of salivary gland masses is controversial compared with other methods. The aim of this work was to evaluate the effectiveness and accuracy of fine-needle aspiration cytology (FNAC) in the diagnosis of parotid gland masses.Material and Methods Over a 10-year period, 126 parotid gland masses were resected. Retrospective chart reviews of 114 patients were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 30 publications
(47 reference statements)
3
55
0
4
Order By: Relevance
“…Many studies from 1987 to 2016 have shown high accuracy (81%‐98%) and high specificity (86%‐100%) for the cytological differentiation between benign and malignant salivary gland lesions, with high sensitivity (73%‐95%) . In the report of Colella et al, the accuracy of salivary FNA for benign tumours including WT was also high (95.6%), as well for non‐neoplastic lesions (94.15%) and also good accuracy was found for malignant tumours (79.95%).…”
Section: Diagnostic Accuracy Of Cytopathology For Salivary Gland Lesimentioning
confidence: 96%
See 2 more Smart Citations
“…Many studies from 1987 to 2016 have shown high accuracy (81%‐98%) and high specificity (86%‐100%) for the cytological differentiation between benign and malignant salivary gland lesions, with high sensitivity (73%‐95%) . In the report of Colella et al, the accuracy of salivary FNA for benign tumours including WT was also high (95.6%), as well for non‐neoplastic lesions (94.15%) and also good accuracy was found for malignant tumours (79.95%).…”
Section: Diagnostic Accuracy Of Cytopathology For Salivary Gland Lesimentioning
confidence: 96%
“…Meta‐analysis of the data for diagnostic accuracy of salivary gland lesion cytopathology in more than 300 publications also shows that all benign salivary lesions were correctly diagnosed in 92.5% of the cases and a false positive was obtained in 3.3% of the cases . According to Klijanienko and Vielh, correct diagnosis of WT as benign lesion was made in 92.1% cases and false positive were obtained in 2.3% cases .…”
Section: Diagnostic Accuracy Of Cytopathology For Salivary Gland Lesimentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, in conclusion, it would be advisable from the standpoint of this theory to consider the data of some works in which much attention is paid to evaluating the effectiveness of diagnostic, prediction and classification methods and the results obtained in them appear to be reliable. One such work was devoted to assessing the effectiveness of the FNAC detection method [15]. The introduction describes the essence of this work, in which the numerical values of many efficiency parameters characterizing this method were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Further, it will be shown that these are fundamentally incorrect judgments, since operating with such canonical concepts as sensitivity and specificity does not lead to an unambiguous assessment of the effectiveness of the methods. Among the works in which the aspect of evaluating the effectiveness of diagnostic methods, prediction and classification is prominent and it seems reliable, should be cited the work of Swedish researchers [15]. The authors of this work set a goal to evaluate the effectiveness of the fine-needle aspiration biopsy method (fine-needle aspiration cytology, FNAC) for diagnosing parotid gland proliferation (parotid gland masses).…”
Section: Evaluation Of the Effectiveness Of Various Methods Of Diagnomentioning
confidence: 99%